Factors Associated with the Nutritional Status among Children Under Five in Lamawalang, Larantuka, East Flores, East Nusa Tenggara - Chintya Claudia Monika Weruin; Marselinus L Nur; Sarci M Toy (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The progress of a country is influenced by the quality of its human resources and can be seen from the degree of health which is a reflection of the health of individuals, groups and communities which is described by life expectancy, mortality, morbidity and nutritional status of the community. Toddlers are the age group that most often suffers from malnutrition or are one of the groups of people who are vulnerable to nutrition. This study aimed to determine the factors related to the nutritional status of toddlers in Lamawalang Village, Larantuka District, East Flores Regency. Subjects and Method: This was an analytical survey with a cross-sectional design which was conducted in Lamawalang Village, Larantuka, East Flores, East Nusa Tenggara from August to September 2022. A total of 54 mothers of toddlers aged 12-59 months were selected for this study. The dependent variable is the nutritional status of children under five. The independent variables were history of exclusive breastfeeding, mother's nutritional knowledge, mother's educational level, mother's occupation and family income. Data were collected using a questionnaire and analyzed using the chi-square test. Results: Lack of maternal knowledge (OR= 135.00; 95% CI= 10.57 to 1723.97; p< 0.001), and not exclusive breastfeeding (OR= 1.88; 95% CI= 1.43 to 2.45; p= 0.019) significantly influence the nutritional status of children under five. Education (OR= 0.85; 95% CI= 0.14 to 0.85; p= 0.891), occupation (OR= 4.07; 95% CI= 0.45 to 36.58; p= 0.182), family income (OR= 0.29; 95% CI= 0.03 to 2.65; p= 0.252) had an effect on the nutritional status of children under five, but not statistically significant. Conclusion: Knowledge and history of exclusive breastfeeding significantly influence the nutriational status of children under five. Keywords: nutritional status, toddlers, maternal knowledge, history of exclusive breastfeeding. Correspondence: Chintya C M Weruin. Study Program in Public Health, Faculty of Public Health, Universitas Nusa Cendana Kupang. Jl. Adisucipto Penfui, Kupang, Nusa Tenggara Timur. Email: Claudiaweruin25@gmail.com. Mobile: +62 822-2914-7039.